The safety of journalists: an assessment of perceptions of the origins and implementation of policy at two international television news agencies - Venter, Sahm (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
Being a journalist today can be a deadly pursuit, particularly for those covering conflict and other dangerous assignments. In 2004 more journalists and other media workers were killed than in the last ten years. While it is impossible to guarantee that journalists will not be killed or injured, kidnapped or detained, a policy has been created to help protect them in the course of their duties. This study examines the perceptions of journalists working for two international television news agencies about this safety policy called the 'Joint code of practice for journalists working in conflict zones'. This policy was adopted in November 2000 by five major television companies including the television news agencies Reuters Television and Associated Press Television News. This study finds that the policy had significant flaws in how it was formulated and how it is communicated, implemented and reviewed. Recognising the existence of unequal relations of power and conflicting interests at play in any policy process, this study stresses that in the case of the journalist safety policy, all stakeholders should have participated in the relevant policy stages. This argument arises from researching the policy document as well as from the point of view of managers, and particularly journalists who work on dangerous assignments, either full-time or on a freelance basis for either of the two television news agencies. It finds that while journalists are not generally aware of the policy, they do practice many of its elements as well as a range of their own custom-made strategies to protect themselves. The result is to make the policy less effective than it could be.
Keywords: Reuters Television; Associated Press Television News; Journalism -- Safety measures; Journalists -- Protection; News agencies -- Safety measures